Pengaruh Pengungkapan Coporate Social Responsibility, Good Corporate Governance, dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Tahun 2021-2023 - Sangadah, Imroatus; Astuti, Puji; Zaman, Badrus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of Corporate Social Responsibility disclosure, Good Corporate Governance, and Company Size on Company Profitability. This study uses a quantitative causality approach. The data used are secondary data in the form of annual financial reports of the food and beverage sub-sector listed on the IDX in 2021-2023. The sampling technique used purposive sampling, so that a sample of 24 companies was obtained. The data analysis technique used multiple linear regression analysis which was tested using SPSS 25. The results of the study show that CSR disclosure partially has a significant positive effect on company profitability. Partially, GCG has no effect on profitability. While company size partially has a significant negative effect on profitability. Simultaneously, CSR Disclosure, GCG, and Company Size affect Company Profitability. Companies are expected to continue to implement and improve CSR disclosure, form audit committees not only to meet formal and regulatory requirements, but also to optimize the function and real contribution of the audit committee itself. And it is hoped that large companies can use their assets efficiently in their company operations, so that the company's profitability is maximized.